Proceedings ILASS–Europe 2017. 28th Conference on Liquid Atomization and Spray Systems 2017
DOI: 10.4995/ilass2017.2017.4951
|View full text |Cite
|
Sign up to set email alerts
|

Fuel spray vapour distribution correlations for a high pressure diesel fuel spray cases for different injector nozzle geometries.

Abstract: The evolution of diesel fuel injection technology, to facilitate strong correlations of in-cylinder spray propagation with injection conditions and injector geometry, is crucial in facing emission challenges. More observations of spray propagation are, therefore, required to provide valuable information on how to ensure that all the injected fuel has maximum contact with the available air, to promote complete combustion and reduce emissions. In this study, high pressure diesel fuel sprays are injected into a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, the insignificant differences are similar to those from the fuel spray liquid penetration studies presented in Figures 17 to 22. Such studies are uncommon in literature; however, an earlier study [34] ascribed the longer fuel spray vapour penetration values usually observed against the fuel spray liquid penetration values at corresponding fuel injection pressure values to the effect of the k-factor. In the present studies, for instance, comparing Figure 21 with Figure 26, the fuel spray vapour penetration is ~ 40% further at 720µs after the start of injection compared to the fuel spray liquid penetration values for both injectors C and D measured at the same time.…”
Section: Spray Liquid and Vapour Penetrationmentioning
confidence: 99%
“…Therefore, the insignificant differences are similar to those from the fuel spray liquid penetration studies presented in Figures 17 to 22. Such studies are uncommon in literature; however, an earlier study [34] ascribed the longer fuel spray vapour penetration values usually observed against the fuel spray liquid penetration values at corresponding fuel injection pressure values to the effect of the k-factor. In the present studies, for instance, comparing Figure 21 with Figure 26, the fuel spray vapour penetration is ~ 40% further at 720µs after the start of injection compared to the fuel spray liquid penetration values for both injectors C and D measured at the same time.…”
Section: Spray Liquid and Vapour Penetrationmentioning
confidence: 99%
“…One of the variants of this modernization is presented in study [4], where the structural change of the outlet nozzles of the sprayer positively influences the improvement of the maximum and medium injection pressure. The variant, described in paper [5], is similar to this approach. According to this work, it was found that the change in the ratio of the diameters of the inlet and outlet sections of the sprayer nozzles makes it possible to adjust the depth of penetration of a fuel jet to the combustion chamber volume and to improve the fuel distribution in it.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The pressure in the inlet and outlet section of the hydraulic corrector is equal to the pressure in its fuel volume. 5. Instantaneous values of the rate of non-constant fuel motion are determined from formulas of constant motion.…”
Section: Refinement Of the Estimation Model Of The Separated Hydraulimentioning
confidence: 99%
“…In the same way that studying the combustion performance of any fuel in an ICE is important, it is also important to describe how the behavior in terms of atomization and spray development is. Both processes are strongly influenced by the physical processes occurring inside the cylinder [8], which at the same time depend on nozzle characteristics and injection-related operating conditions. Parameters such as injection pressure, needle lift, orifice conicity or orifice geometry control flow dynamics and behavior at the outlet of the nozzle [9][10][11].…”
Section: Introductionmentioning
confidence: 99%